2015
DOI: 10.5089/9781484356869.001
|View full text |Cite
|
Sign up to set email alerts
|

Credit Booms and Macroeconomic Dynamics: Stylized Facts and Lessons for Low-Income Countries

Abstract: Using a comprehensive database on bank credit, covering 135 developing countries over the period 1960-2011, we identify, document, and compare the macroeconomic dynamics of credit booms across low-and middle-income countries. The results suggest that while the duration and magnitude of credit booms is similar across country groups, macroeconomic dynamics differ somewhat in low-income countries. We further find that surges in capital inflows are associated with credit booms. Moreover, credit booms associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 12 publications
4
33
0
1
Order By: Relevance
“…A significant body of research has tried to comprehend the economic determinants of abnormal credit growth and has successfully identified some relevant macroeconomic factors that are associated with the credit dynamics (Gourinchas, Valdes and Landerretche, 2001;Barajas, Dell'Ariccia and Levchenko, 2009;Arena et al, 2015;Dell'Ariccia et al, 2016;Meng and Gonzalez, 2017;Avdjiev, Binder and Sousa, 2018). However, the strict focus on economic determinants, neglecting other potential drivers, is a shortcoming found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A significant body of research has tried to comprehend the economic determinants of abnormal credit growth and has successfully identified some relevant macroeconomic factors that are associated with the credit dynamics (Gourinchas, Valdes and Landerretche, 2001;Barajas, Dell'Ariccia and Levchenko, 2009;Arena et al, 2015;Dell'Ariccia et al, 2016;Meng and Gonzalez, 2017;Avdjiev, Binder and Sousa, 2018). However, the strict focus on economic determinants, neglecting other potential drivers, is a shortcoming found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…9 Mendoza and Terrones (2008), Elekdag and Wu (2011), and Arena et al (2015), also found that growth tends to rise before booms and decline towards the end of it. Jorda et al (2013) further suggest that faster credit growth tends to be followed by deeper recessions and slower recoveries.…”
Section: Credit Booms Before Deleveraging Episodes C Duration Of mentioning
confidence: 99%
“…Using a looser boom identification strategy, Elekdag and Wu (2011) found the ratio to be about 3 percent. Arena et al (2015), Dell' Ariccia et al (2014), andMendoza andTerrones (2008) found the frequency of credit booms to be about 2 percent.…”
Section: Credit Booms Before Deleveraging Episodes C Duration Of mentioning
confidence: 99%
“…A number of studies employ statistical techniques, for example, Terrones (2008, 2012), Gourinchas, Valdes and Landarretch (2001), Barajas, Dell'Ariccia andLevchenko (2009), Tornell andWestermann (2002), IMF (2011), Dell'Ariccia et al (2012, and Arena et al (2015). They compare a country's credit-to-GDP ratio or real credit per capita to its nonlinear trend and determine the episodes of credit booms when the positive deviations from trend pass a certain threshold.…”
Section: Identification Of Credit Boom Episodesmentioning
confidence: 99%
“…For instance, IMF (2011) applies a panel logit model with 47 advanced and emerging market economies to study the underlying factors leading to credit booms; and finds that financial sector reforms, TFP gains, and in particular, net capital inflows appear to be good predictors of credit booms. Similarly, the study of Arena et al (2015) on 135 middle-and low-income countries using event analysis and panel probit regression suggests that capital inflows are important determinants of credit boom episodes in middle-and low-income countries. Particularly with event analysis, countries with less flexible exchange rates may experience significant credit growth at the time of capital inflow surges, while financial openness can also trigger credit booms.…”
Section: Introductionmentioning
confidence: 99%